1971
DOI: 10.1002/jctb.5020210403
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration at anatase titanium dioxide surfaces by organic contamination

Abstract: A major t'ause of vacuum discoloration of some anatase titanium dioxide powders at 5 x 10-2 torr has been iden:ifed as contamination by rotary pump oil. The discoloration is stable in dry air but fades on exposure to moist air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…While catechol molecules attach very strongly by bidentate polar covalent bonds, other hydroxyl groups attach to the TiO 2 surface by looser bidentate or monodentate bonds (1520, 24). The doxorubicin molecule falls into the later category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While catechol molecules attach very strongly by bidentate polar covalent bonds, other hydroxyl groups attach to the TiO 2 surface by looser bidentate or monodentate bonds (1520, 24). The doxorubicin molecule falls into the later category.…”
Section: Resultsmentioning
confidence: 99%
“…Below 20 nm the physical strain on the titanium-oxygen bonds on the nanoparticle surface causes high reactivity: these bonds can be broken easily to form stable polar covalent bonds with hydroxyl groups of catechol ligands such as dopamine and Alizarin Red S (1014). At the same time, surface TiO 2 molecules form less stable bonds with other hydroxyl group -containing molecules (1520). We found that the interaction between the TiO 2 surface and doxorubicin is relatively labile and is pH-dependent and show several lines of evidence for doxorubicin dissociation from nanocomposites inside cells.…”
Section: Introductionmentioning
confidence: 99%